The influence of Syubhah semi processed food knowledge on consumer purchase behavior / Reezlin Abd Rahman - Abd Rahman, Reezlin (2017)
No exaggeration that Muslim consumers around the world with regard to food undeniably put their greater concern on the three concepts that are halal, haram and Syubhah or doubtful. In this sense, Muslim consumers are ascertained that the food products obtained or buying from any market place should religiously fit for their consumption or complied with Islamic regulation. The concern on these three concepts directly relate with the ingredients used, preparation and cleanliness of the products either on dry, wet, fresh, canned or processed food. In other words, the halal, haram and syubhah are the important religious elements in shaping Muslim consumer attitudes that influence their food purchasing behavior. Despite these, most of the available studies are dealing with halal food products, halal certification, halal logo, halal quality assurance and halal consumer awareness with less investigation particularly looking at the cause and affect between Syubhah semi- processed food and Muslim consumers purchase behavior. In filling the gap, hence this study is empirically examining the causal relationship between knowledge on syubhah semi processed food attributes and semi and-rural Muslim consumers purchase behavior. With that, a causal research design using the quantitative approach was used and the semi and rural consumers in the Kedah state was chosen as a sample of the study. Through a self-administered survey, 780 usable questionnaires were successfully collected. With the various statistical analyses ranging from frequency, descriptive, inferential and the Multivariate Structural Equation Modelling (SEM) via Partial Least Square (PLS- SEM) used to answer the research objectives, research questions and hypotheses, some useful insights pertaining to the issues investigated was significantly obtained. The results provide evidences that there is a linkage between knowledge of syubhah semi processed food attributes and consumer purchase behaviour. In detail, lack of knowledge or ignorance on the composition of ingredients, wholesomeness, labelling and certification cause the Muslim consumers in semi and rural areas of purchasing the syubhah semi processed food products. It is interesting to revealed that lack of knowledge on the composition of ingredients, wholesomeness, labelling and certification has elevated the trust among the Muslim consumers in the semi and rural area in turn translate their confident toward purchasing the syubhah or doubtful semi processed food products. Another remarkable finding is that the translation of trust toward purchasing the syubhah or doubtful semi processed food products are also influence through the influence of others either families, friends or other consumers and brand equity which relate to halal logo and Islamic symbol although these elements are being manipulated or fake. These pessimistic indications from the practical aspects carry varying consequences and implications for the Muslim consumers, the semi processed food producers that closely and the relevant authorities particularly State. The remarkable findings from this study indicated that without knowledge on the characteristic of the products, consumers still purchase the product although they are still in the doubtful stage due to the influence of trust.